Inulin Exerts Beneficial Effects on Non-Alcoholic Fatty Liver Disease via Modulating gut Microbiome and Suppressing the Lipopolysaccharide-Toll-Like Receptor 4-Mψ-Nuclear Factor-κB-Nod-Like Receptor Protein 3 Pathway via gut-Liver Axis in Mice - Bao, Ting; He, Fang; Zhang, Xiaoxia; Zhu, Lili; Wang, Zhen; Lu, Haixia; Wang, Ting; Li, Yiwei; Yang, Shaoqi; Wang, Hao (Frontiers in Pharmacology, 2020)
Background: Non-alcoholic fatty liver disease (NAFLD) is a common metabolic disorder disease worldwide with chronic low-grade inflammation and alteration of gut microbiota. Inulin (INU) has been confirmed to be beneficial for metabolic diseases. The aim of this study was to clarify the effects and mechanism of INU protecting for NAFLD inflammation via gut-liver axis. Methods: C57BL/6 mice were randomly divided into four groups: normal diet group (ND); high-fat diet group (HFD); ND with INU group (ND-INU); HFD with INU group (HFD-INU). After 14 weeks of feeding, mice were sacrificed and associated indications were investigated. Results: Significant increases of body weight, liver weight, liver biochemical AST, ALT, TG, TC, and pro-inflammatory indicators (LPS, IL-18, IL-1β, TNF-ɑ and IL-6) as well as a reduction of plasma IL-10 were observed in HFD group, while INU treatment restored these abnormal indicators. The ratio of hepatic macrophages (Mψs) and TLR (Toll-like receptor) 4+ Mψs were both reduced with INU administration. Notable reductions of nuclear factor-κB (NF‐κB), nod-like receptor protein 3 (NLRP3), apoptosis-associated speck-like protein (ASC) and caspase‐1 were showed in HFD-INU group. 16S rRNA sequencing and analysis of gut microbiota showed the reductions of Akkermansia, Bifidobacterium, as well as the enhancement of Blautia in HFD group compared to ND, while increased Akkermansia, Bifidobacterium, and a reduction of Blautia were measured with INU. Increases of short-chain fatty acids including acetic, propionic and butyric acids, were determined with INU. Conclusion: INU prevents NAFLD via moderating gut microbiota and suppressing LPS-TLR4-Mψ-NF-κB-NLRP3 inflammatory pathway through gut-liver axis.